Skip to content
Related Articles

Related Articles

Improve Article
Save Article
Like Article

Class 9 NCERT Solutions – Chapter 4 Linear Equations in two variables – Exercise 4.1

  • Last Updated : 23 Feb, 2021

Question 1. The cost of a notebook is twice the cost of a pen. Write a linear equation in two variables to represent this statement.

Solution:

Let’s take the cost of a notebook as Rs. x and the cost of a pen as Rs. y.

Attention reader! All those who say programming isn't for kids, just haven't met the right mentors yet. Join the  Demo Class for First Step to Coding Coursespecifically designed for students of class 8 to 12. 

The students will get to learn more about the world of programming in these free classes which will definitely help them in making a wise career choice in the future.

Given that cost of a notebook (x) is twice the cost of a pen(y). 



So, x = 2y.

x – 2y = 0

x – 2y = 0 is the linear equation in two variables that represent the statement.

Question 2. Express the following linear equations in the form ax + by + c = 0 and indicate the values of a, b and c in each case: 

(i) 2x + 3y = 9.35 

Solution:

2x + 3y – 9.35 = 0 (Transposing 9.35 to LHS)

(2)x + (3)y + (-9.35) = 0 (converting it in the form ax + by + c = 0)

On comparing equation with ax + by + c = 0, 



We get a = 2, b = 3, c = -9.35

(ii) x – y/5 -10 = 0

Solution:

(5x – y – 50)/5 = 0 (Multiply and divide the whole equation by 5)

5x – y – 50 = 0

(5)x + (-1)y + (-50) = 0 (converting it in the form ax + by + c = 0)

On comparing equation with ax + by +c =0, 

We get a = 5, b = -1, c = -50

(iii) -2x + 3y = 6

Solution:

-2x + 3y – 6 = 0 (Transposing 6 to LHS)

(-2)x + (3)y+ (-6) = 0 (converting it in the form ax + by + c = 0)

On comparing equation with ax + by +c =0, 

We get a = -2, b = 3, c = -6

(iv) x = 3y

Solution:

x – 3y = 0 (Transposing 3y to LHS)

(1)x + (-3)y + 0 = 0 (converting it in the form ax + by + c = 0)

On comparing equation with ax + by + c = 0, 

We get a = 1, b = -3, c = 0



(v) 2x = -5y

Solution:

2x + 5y = 0 (Transposing 5y to LHS)

(2)x + (5)y + 0 = 0 (converting it in the form ax + by + c = 0)

On comparing equation with ax + by +c =0, 

We get a = 2, b = 5, c = 0

(vi) x + 2 = 0

Solution:

(1)x + (0)y + 2 = 0 (converting it in the form ax + by + c = 0)

On comparing equation with ax + by +c =0, 

We get a = 1, b = 0, c = 2

(vii) y – 2 = 0

Solution:

(0)x + (1)y + (-2) = 0 (converting it in the form ax + by + c = 0)

On comparing equation with ax + by +c =0, 

We get a = 0, b = 1, c = -2 

(viii) 5 = 2x

Solution:

5 – 2x = 0 (Transposing 2x to LHS)

(-2)x + (0)y + 5 = 0 (converting it in the form ax + by + c = 0)

On comparing equation with ax + by + c = 0, 

We get a = -2, b = 0, c = 5

My Personal Notes arrow_drop_up
Recommended Articles
Page :